Effect of Cu foam on the microstructure and strength of the SiCf/SiC-GH536 brazed joint. Issue 9 (1st May 2022) - Zhang, Yu; Guo, Xuming; Guo, Wei; Zhang, Hongqiang; Shao, Tianwei; Yu, Ziliang
Abstract: The AgCuTi filler and Cu foam interlayer were used to braze silicon carbide fiber-reinforced silicon carbide matrix composites (SiCf /SiC) and nickel-based superalloy. Cu foam interlayer could reduce the brittle reaction layer on the SiCf /SiC side by diluting the brazing seam by producing Cu-based solid solution (Cu(s, s)) to inhibit Ti diffusion from the brazing filler. Cu foam did not completely disappear in the brazed joints and still maintained the basic skeleton. Sound SiCf /SiC-GH536 joints were obtained with AgCuTi filler at 890 °C for 10 min. Compared to the brazed joints without Cu foam, introducing Cu foam could enhance the overall shear strength of the brazed joints by 224%. Cu foam buffer layers provided a technique for increasing the mechanical properties of joints, promoting the use of SiCf /SiC composites in a wide range of applications.